(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Description of nutritional status and some factors related to malnutrition in the elderly at An Giang Central General Hospital in 2023. Subjects and method research: Design cross-sectional descriptive study with an analysis of 260 elderly people in inpatient treatment at An Giang Central General Hospital. Information was collected by a set of prepared questionnaires through face-to-face interviews. Results: Malnutrition in the elderly accounted for 44.2% and women were more malnourished. The study found factors related to malnutrition, such as age, drug use, skin condition and nutritional consumption (p<0.05). People with dental problems had a higher rate of malnutrition 51.4%, without dental problems, at 7.1% (p<0.05). Conclusions: Malnutrition rate is still high in the elderly (44.2%). Age, medication use, dental disease and protein deficiency are related to malnutrition. Therefore, screening for malnutrition in the elderly should be done from admission. From there, conduct nutritional interventions in a timely manner with more appropriate and effective measures.